The Relationship between the Ownership Structure, Capital Structure and Performance - Al-Thuneibat, Ali (JABM JOURNAL of ACCOUNTING - BUSINESS & MANAGEMENT, 2018)
This paper aims at providing an empirical evidence concerning the relationship between the ownership structure, capital structure and financial performance of the shareholding companies listed in Amman Stock Exchange (ASE). To measure the ownership structure, the researcher used four variables including foreign, institutional, managerial and concentrated ownership. The capital structure is measured by using the leverage, and the performance is measured by using the return on assets (ROA). To achieve the objectives of the study, a sample of 86 firms from the industrial and service companies listed in ASE during the period 2010 and 2014 is used. The results of the study showed that the relationship between ownership structure in general, and performance is positive and statistically significant, however, the results showed that the various types of ownership structure have different types of relationships with performance. More specifically, there is a negative impact of institutional and foreign ownerships on the performance and positive impact of concentrated and managerial ownerships. The results also revealed that there is a positive impact of the financial leverage on the relationship between ownership structure and firm performance. The findings of the study provide implications to the regulators, investors and managers in Jordan to take into consideration the environment-specific factors when developing corporate regulations and encourage concentrated and managerial ownership because they have positive impact on performance.